Clinical Epidemiological Look at Patients with Congenital Heart Disease: a Study that has Become a Priority - Jan O´neil González Ramos; Nancy González Vales; Eida María Mena Albernal; Elsy Roxana Geroy Moya; Nicolás Ramón Cruz Pérez; Annia Quintana Marrero (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: congenital heart diseases are the most serious congenital anomalies in the newborn, with a great impact on pediatric morbidity and mortality. The most frequent are the interventricular and interatrial communication. Objective: to characterize the patients with ventricular septal defect and atrial septal defect at the Paquito González Cueto University Pediatric Hospital in Cienfuegos. Method: descriptive cross-sectional study carried out in the cardiology clinic of the Paquito González Cueto University Pediatric Hospital in Cienfuegos from January 2008 to December 2018. The universe was represented by 120 patients with interventricular or interatrial communication who were treated in the Cardiology Service in the outpatient clinic of the center. The variables analyzed were: age, sex, age at diagnosis, type of heart disease, type of interventricular and interatrial heart disease defect, maternal risk factors, fetal risk factors, extra cardiovascular malformations, clinical presentation, forms of defect resolution. Statistical analysis was performed using the SSPS 15.0 program and the results are shown in tables. Results: ventricular septal defect was the most frequent. The male sex and the age group 1-4 years of age was the most representative, most of the cases were diagnosed between the second week after birth and three months after birth. The maternal risk factor with the highest incidence was arterial hypertension, the most frequent inheritance and presentation was the murmur. Surgery was the predominant form of resolution, genetic diseases were the most frequent fetal risks. The hemodynamic repercussion was present in most of the patients. Conclusions: ventricular septal defect, male sex, and age group 1-4 years were the most representative, the maternal risk factor with the highest incidence was arterial hypertension, surgery was the predominant form of resolution, and genetic diseases were found to be fetal risks.